223 The effects of supplemental zinc and ractopamine hydrochloride on the Longissimus dorsi proteome of finishing beef steers - Hochmuth, Katherine (J Anim Sci, 2020)
The objective of this study was to determine how steer growth rate and Zn nutrition affects the muscle proteome. Forty-eight, high percentage Angus steers (494 ± 18.2 kg) were blocked by BW and GeneMax gain score (GeneMax Focus, Zoetis, Parsippany, NJ) to treatments arranged in a 2×2 factorial. On d 0, steers were assigned to control (CON; 36 mg Zn/kg dry matter [DM]) or supranutritional Zn (SUPZN; CON + 60 mg Zn/kg DM as ZnSO(4)+ 60 mg Zn/kg DM as Zn-amino acid complex) dietary treatment (ZNTRT), and housed in pens (n = 6 or 8 steers/pen) with Growsafe bunks. On d 62, within ZNTRT steers were assigned to ractopamine hydrochloride treatments (RACTRT) of 0 (NO) or 300 mg·steer(-1)·d(-1)(RAC) for 28 d. Longissimus dorsi biopsies (between 12(th)and 13(th)rib) were collected on d 77. Sarcoplasmic fractions were extracted and submitted for proteomics analysis using mass spectrometry (LC-MS/MS). Data were log transformed and comparisons made using t-tests with adjusted P-value cutoffs of 0.1. Differences were noted in abundance of proteins involved in glycolytic, retinol and fatty acid metabolism. A shift from slow to fast muscle fiber type was suggested by decreased abundance of myoglobin and slow skeletal troponin 1 in steers fed RAC compared to steers not fed RAC within CON (P ≤ 0.04), while these proteins also tended to be lesser due to SUPZN within steers not fed RAC (P ≤0.09). The intermediate filament associated protein, vimentin, tended to be less abundant in RAC steers (P ≤ 0.09), suggesting RAC affects cellular remodeling. Proteins involved in immune function were also affected; for instance, the acute phase protein alpha-1-acid glycoprotein was more abundant in CON-RAC compared to either SUPZN-RAC (P = 0.001) or CON-NO (P = 0.02). Ractopamine hydrochloride and supranutritional Zn, independently and collectively, affect proteins involved in muscle metabolism, cellular remodeling and immune function in beef steers.